Chemical, morphological and mechanical analysis of sisal fiber-reinforced recycled high-density polyethylene composites (eXPRESS Polymer Letters, 2010)
Natural fibers are widely used as plastic composite material reinforcements. In this work, composites of postconsumer high-density polyethylene (HDPE) reinforced with sisal fibers were prepared. PE and sisal fibers were chemically modified to improve their compatibilities, try to increase the hydrophobic character of the sisal fiber and hydrophilic character HDPE. Sisal was mercerized with a NaOH solution and acetylated and the PE was oxidized with KMnO4 solution. The chemically modified fibers were characterized by Fourier Transformed Infrared Spectroscopy (FTIR) and 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR). The composites were prepared by extrusion of modified and unmodified materials containing either 5 or 10 wt% fibers. The morphology of the obtained materials was evaluated by SEM. The fiber chemical modification improves it adhesion with matrix, but not benefit were obtained with HDPE oxidation. Flexural and impact tests demonstrated that the composites prepared with modified sisal fibers and unmodified PE present improved mechanical performance compared to pure PE.